Production and Consumption in the Islamic Economy: Muslim Producer and Consumer Behavior - Fitri Ramdani; Muslimin Kara (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
This research aims to analyze the concept of production and consumption in Islamic economics and examine the behavior of Muslim producers and consumers based on sharia values. The research uses a library research method with a qualitative descriptive approach. Data was obtained from various secondary sources in the form of books, scientific articles, and journals relevant to the research theme. Data analysis is carried out through the process of collecting, grouping, and interpreting various literature related to production and consumption activities in the perspective of Islamic economics. The results of the study show that production activities in the Islamic economy are not only oriented to maximize profits, but are also directed to realize the benefits, justice, and welfare of the community in accordance with sharia principles. Muslim producers are required to apply the values of honesty, responsibility, and produce halal and useful goods and services. Meanwhile, consumption behavior in the Islamic economy is based on the principles of halal, tayyib, balance, and the avoidance of excessive behavior (israf) and extravagance (tabdzir). The rationality of Muslim consumers is not only aimed at obtaining material satisfaction, but also considers the spiritual aspects and achievements of the sharia maqashid. Thus, production and consumption in the Islamic economy reflect the integration of economic goals and moral values aimed at creating just and sustainable welfare.